2018
DOI: 10.1080/08870446.2018.1494832
|View full text |Cite
|
Sign up to set email alerts
|

How highlighted utensils influence consumption in a dark setting

Abstract: Difficulty to maneuver should be considered when investigating eating behaviour under dark conditions. In line with an embodied cognition account, results also reveal the necessity of visual information for interaction with objects in the environment and imply that detail-deprived object information may be sufficient for activation of the motor system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the context of food and health, an activation of motor action has been examined (Stok et al, 2018). Förster (2003) found that individuals consumed less of an indulgent drink when their arms were extended, in line with the avoidance‐oriented behavior.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the context of food and health, an activation of motor action has been examined (Stok et al, 2018). Förster (2003) found that individuals consumed less of an indulgent drink when their arms were extended, in line with the avoidance‐oriented behavior.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%